Functionalized Erythrocyte Membrane-Coated Nanoparticles for the Treatment of Klebsiella pneumoniae-Induced Sepsis - Liu, Jun; Ding, Hui; Zhao, Mingjie; Tu, Fan; He, Tian; Zhang, Lizhu; Jing, Yanfei; Rui, Xiaohong; Zhang, Shiliang (Frontiers in Microbiology, 2022)
Sepsis is a systemic inflammatory response syndrome caused by infection, with high incidence and mortality. Therefore, it is necessary to carry out an effective anti-infection treatment. In this work, we designed and synthesized red blood cell (RBC) membrane-coated PLGA nanoparticles named γ3-RBCNPs, which target the highly expressed intercellular adhesion molecule-1 (ICAM-1) at the site of infection through the γ3 peptide on its surface and kill the Klebsiella pneumoniae through ciprofloxacin encapsulated in its core. In addition, the homogenous RBC membrane coated on the surface of the nanoparticles helps them avoid immune surveillance and prolong the circulation time of the drug in the body. We found that the γ3-RBCNPs target HUVECs activated by TNF-α in vitro and the infected lung of mice in the sepsis model very well. In vitro evaluation suggested that γ3-RBCNPs have a low risk of acute hemolysis and are less likely to be engulfed by macrophages. In vivo evaluation showed that γ3-RBCNPs has a long half-life and good bio-safety. More importantly, we confirmed that γ3-RBCNPs have the good antibacterial and anti-infection ability in vivo and in vitro. Our research provides a new strategy for the nano-drug treatment of Klebsiella pneumoniae-induced sepsis.